Surgical treatment of cranial cruciate ligament disease in dogs using Tibial Plateau Leveling Osteotomy or Tibial Tuberosity Advancement–A systematic review with a meta-analytic approach - Wemmers, Annika Christina; Charalambous, Marios; Harms, Oliver; Volk, Holger Andreas (Frontiers in Veterinary Science, 2022)
Tibial Plateau Levelling Osteotomy (TPLO) or Tibial Tuberosity Advancement (TTA) are commonly used surgical techniques for correction of cranial cruciate ligament (CCL) rupture in dogs. This systematic review aims to investigate whether one technique is superior to the other. Seventy-two studies on surgical management of CCL rupture have been identified and evaluated in regard of subjective and objective gait analysis criteria, development of osteoarthritis (OA), thigh circumference measurements, goniometry, joint stability, pain and complication rates. Almost half (47.2 %) of the studies were considered of low quality of evidence, leading to high heterogeneity in quality among studies; this posed a major limitation for an evidence-based systematic review of both surgical techniques. Out of 72 studies, there were only eleven blinded randomized clinical trials, of which five were rated with a low overall risk of bias. However, both techniques were considered to be successful management options. Subjective and objective gait analysis revealed no lameness at long-term evaluation for the majority of the patients. However, it appeared that TTA lead to better OA scores up to 6 months postoperatively, while TPLO had a lower rate of surgical site infections. In summary, no method can be clearly preferred, as most of the study evaluated were subpar. Studies with a high level of evidence are therefore urgently needed for such a common surgical procedure.